Liberalisation and universal access to basic services : Telecommunications, water and sanitation, financial services, and electricity - Organisation for Economic Co-operation and Development; World Bank (Paris : OECD, 2006)
Building on a recent groundbreaking OECD/World Bank seminar, this volume explores whether and how trade liberaliaation can contribute to achieving universal service goals and the types of complementary policies required. It focuses on experiences in four sectors: telecommunications, water and sanitation, financial services, and electricity. A horizontal assessment also helps determine how far the current services negotiations in the WTO, under the General Agreement on Trade in Services, can aid the attainment of universal service goals.--Publisher's description
pt. 1. Telecommunications. Universal access to telecommunications in a competitive environment / by Patrick Xavier -- Uganda's approach to universal access to telecommunications / by F.F. Tusubira -- India's experience wiht universal service obligations in telecommunications / b Harsha Vardhana Singh -- pt. 2. Water and sanitation. Universal access in the water and sanitation sector / by Robin Simpson -- Reflections on the goal of universal access in the ater and sanitation sector : lessons learned from Ghana, Sengal and Nepal / by Dale Whittington -- Efficiency, equity and liberalisation of water services in Buenos Aires, Argentina / by Miguel Solanes -- pt. 3. Financial services. Universal acccess to financial services : a review of the issues and public policy objectives / by Stijn Claessens -- Provision of financial services in South Africa / by Mark Napier -- Regulatory aspects of universal access to financial services in India / by Bindu Ananth and Ncahiket Mor -- pt. 4. Electricity. Power sector librealisation, the poor and multilateral trade commitments / by Peter C. Evans -- Power sector liberalisation and access to energy in the Philippines / by Romeo Pacudan
Includes bibliographical references
Keywords: Public utilities -- Government policy; Financial services industry -- Government policy